Environmental comfort based (ECB) methodology as a tool for preparing Kaizen application in a catering service company. Issue 4 (10th April 2018) - Jaca, Carmen; Ormazabal, Marta; Viles, Elisabeth; Santos, Javier
Abstract : Purpose: The purpose of this paper is to develop a methodology that is based on the concept of environmental comfort and can serve as a tool that can help companies and employees to implement Kaizen projects. This methodology focuses on the worker's participation in analyzing and developing improvements related to their workplace. Design/methodology/approach: This research is focused on the development of a methodology that encourages worker participation in improvement activities, through the analysis of their working conditions. For this purpose, the proposed methodology was developed in accordance with the dimensions of workplace comfort proposed by Vischer. The employees start working on the analysis of problems and their solutions through the logical framework approach, as it is a tool that encourages worker participation and consensus. The developed methodology was applied in a company, with three different groups of people, which enabled the authors to test its utility. Findings: The findings reveal that the proposed methodology is effective in initiating workers in the path of Kaizen. The employees who applied this methodology were able to propose improvement actions that addressed the problems and opportunities that they had previously detected. Moreover, the questionnaire that was used to validate the methodology and was administered to employees shows that the methodology is useful in preparing them for adopting continuous improvement (CI) programs. Research limitations/implications: The methodology presented in this paper has been applied and evaluated by a small number of employees. These limitations suggest future research recommendations. Practical implications: This participatory methodology could be used by different types of companies to initiate employees on the path of CI, even if they are not familiar with improvement programs or methodologies. In addition, its use could improve the capabilities of employees in areas such as participatory analysis, problem identification and proposal of objectives. These capabilities are necessary in any Kaizen project. As a result of the application of this methodology, the companies could obtain a list of areas of improvement related to their work and propose actions to work on. Originality/value: The paper presents the use of environmental comfort in the workplace as the first step in accomplishing a Kaizen project, with a focus on the employee involvement and consensus.